Les paradoxes apparents de l'expansion papetiere en Indonesie: ne exploration des liens finance-gouvernance-environnement pour l'analyse d'un secteur en termes de durabilite - Pirard, R. (Ecole des Hautes Etudes en Sciences Sociales, 2006)
The rapid expansion of the Pulp & Paper industry in Indonesia has generated large overcapacities because fiber supplies were based mainly on the conversion of tropical forests. Using financial theory about financial expropriation and debt entrenchment in East Asia, it shows that the ultimate owners of the groups have been able to capture most of the rents owing to a divergence between their control rights and their ownership rights. Their profits were done in the short term, but their costs were postponed owing to a capital structure based on debts. Politics and public governance have also played an important role in favor of the interests of the ultimate owners, and all the apperances seem to suggest that the expansion followed a model of political economy. Recent efforts to develop large-scale fast-growing plantations have poor impacts on the sustainable developement of the rural areas, because of environmental irreversibilities and a loss of flexibility for the rural poor. However, economic irreversibilities lower the probability that the current trend be voluntarily modified.